Interrelationships of growth hormone AluI polymorphism, insulinresistance, milk production and reproductive performance in Holstein-Friesian cos - O. Balogh; O. Szepes; K. Kovacs; M. Kulcsar; J. Reiczigel; J.A. Alcazar; M. Keresztes; H. Febel; J. Bartyik; S. Gy. Fekete; L. Fesus; Gy. Huszenicza (Veterinární Medicína, 2008)
Healthy multiparous Holstein-Friesian cows (n = 22, parity: 2-4) from a large-scale dairy herd in Hungary were subjected to an intravenous glucose tolerance test 10-15 days after calving. AluI genotype of growth hormone, several plasma metabolites and metabolic hormones were determined, and current and previous lactation yields were recorded. We also used the Revised Quantitative Insulin Sensitivity Check Index (RQUICKI) and its modified version (RQUICKIBHB) for the estimation of peripheral insulin sensitivity. The majority of cows (n = 18) was leucine homozygous (LL), four were heterozygous (LV) and there were no valine homozygous (VV) animals in the population. Current average milk production was not different between AluI genotypes, but LV cows tended to have higher 305-day previous lactation yields (P = 0.13). AluI polymorphism was not associated with any of the calculated glucose and leptin parameters of the intravenous glucose tolerance test (P > 0.58). Heterozygous cows were prone to higher basal insulin levels (P = 0.064), longer time to reach half of the maximal and basal insulin concentrations (P = 0.035 and P = 0.054, respectively) and larger insulin area under the curve (P = 0.032). Both RQUICKI and RQUICKIBHB estimated decreased insulin sensitivity in LV compared to LL cows (P = 0.055 and P = 0.044, respectively). Higher plasma NEFA and BHB levels accounted for slower glucose disappearance and lower insulin release and insulin clearance rate (P < 0.05). Average yield was inversely related to glucose area under the curve (P = 0.040) and time to reach baseline concentration (P = 0.005). Plasma cortisol lowered glucose clearance rate (P = 0.040) and prolonged time to reach basal levels (P = 0.006). More weight loss was associated with higher glucose peak and prolonged glucose disappearance time (P = 0.055 and P = 0.024, respectively). All cows became cyclic and showed signs of estrus during the study period. There were no differences between leucine homozygous and heterozygous animals in the onset of ovarian activity and in the time of first observed estrus (P > 0.540). We conclude that Holstein-Friesian cows heterozygous for AluI polymorphism of the growth hormone gene may be more likely to develop insulin resistance during early lactation than leucine homozygous cows. Decreased insulin sensitivity could be part of a homeorhetic adaptation process that supports nutrient partioning for the use of the mammary gland and may allow LV cows to reach higher yields throughout lactation.